2017
DOI: 10.9767/bcrec.13.1.1152.144-154
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Control of NOx-Soot by Substitutions of Ag and K on Perovskite (LaMnO3) Catalyst

Abstract: The different Ag and K substituted perovskite catalysts including base catalyst were LaMnO3 by the solid state method and the diesel soot was prepared in the laboratory. Their structures and physicochemical properties were characterized by X-ray diffraction (XRD), BET, SEM, H2-TPR, and XPS techniques. The Ag Substituted at A-site perovskite structured catalysts are more active than other type of catalysts for the simultaneous soot-NOx reaction, When Ag and K are simultaneously introduced into LaMnO3 catalyst, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…In general, it can be seen that all catalytic systems showed very good performance in soot oxidation compared to the non-catalytic one according to the following order in activity LaAgMnO3 (NO/O2) > LaMnO3 (NO/O2) > LaAgMnO3 (O2) > non-catalytic (NO/O2). Similar trends were obtained by Dhal et al [13], who evaluated the effect of Ag and K substitutions on LaMnO3 catalyst in the simultaneous removal of NOx and soot. They have found that soot combustion, as well as, the NOx reduction by soot greatly increase by the presence of metallic silver in the catalyst.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 86%
See 2 more Smart Citations
“…In general, it can be seen that all catalytic systems showed very good performance in soot oxidation compared to the non-catalytic one according to the following order in activity LaAgMnO3 (NO/O2) > LaMnO3 (NO/O2) > LaAgMnO3 (O2) > non-catalytic (NO/O2). Similar trends were obtained by Dhal et al [13], who evaluated the effect of Ag and K substitutions on LaMnO3 catalyst in the simultaneous removal of NOx and soot. They have found that soot combustion, as well as, the NOx reduction by soot greatly increase by the presence of metallic silver in the catalyst.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 86%
“…Exhaust-after-treatment devices and engine modifications have been implemented to reduce the NOx and soot emissions from diesel engines [5][6][7][8][9]. However, for the simultaneously removal of soot and NOx, it is not enough to consider only engine modifications, and the implementation of diesel particle filter combined with catalytic combustion technology appears to be the most practical method to reduce the emission of these harmful substances [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the soot-to-catalyst ratio was systematically examined elsewhere . The effect of contact between soot and catalyst was specifically investigated in refs , and a broad scope of the reported ranges of the soot-to-catalyst mass ratios can be classified into three arbitrary categories: Low soot content mixtures: 1:20, ,,,,, 1:19, and 1:15. , Medium soot content mixtures: 1:10, ,,,,,,,, 1:9, ,,,− ,,,, and 1:8. High soot content mixtures: 1:5, 1:4, , and 1:1 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the dual substitution of Ag and K in place of La in LaMnO 3 has been demonstrated giving improved activity in the simultaneous soot-NO x reaction [41]. As a matter of fact, soot combustion is largely accelerated, with the temperature for maximal soot conversion (T m ) lowered by at least 50 • C; moreover, the silver substitution at A site of perovskite increases the NO x reduction efficiency (Table 6).…”
Section: Catalyst T I No X Conversionmentioning
confidence: 99%